Development of Amil Zakat Training Concept Using Islamic Approach in Indonesia - Salamun, Ade; Hafidhuddin, Didin; Bahruddin, E.; Alim, Akhmad (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
One of the efforts to improve Amil Zakat's competence is by providing training. This article aims to examine the concept of amil zakat training and the development efforts that can be made. This article is made by using the literature method with a descriptive-analytical approach. The study's result shows that Amil Zakat's existing training condition only prioritizes Amil's technical ability and work attitude. There is no specific curriculum related to character education, but character education has been inserted into learning activities. The effort to develop amil zakat training can be made by designing amil zakat training that is not only competency-based but also adab-based so that amil zakat who take part in the training are not only competent in the work of managing zakat but also competent as individual Muslims.